An autonomy viability assessment matrix for agent-based autonomous systems - Mostafa S.A.; Ahmad M.S.; Ahmad A.; Annamalai M.; Gunasekaran S.S. (Institute of Electrical and Electronics Engineers Inc., 2023)
Multi agent systems; Robotics; Software agents; Agent based; Assessment matrixes; Autonomous systems; autonomy assessment; Different domains; Situation awareness; Autonomous agents